Evaluation of the anatomic and hemodynamic abnormalities in tricuspid atresia before and after surgery using computational fluid dynamics - Chen, Li-Jun (Medicine (Baltimore), 2018)
Analysis of hemodynamics inside tricuspid atresia (TA) chamber is essential to the understanding of TA for optimal treatment. In this study, we introduced a combined computational fluid dynamics (CFD) to simulate blood flow in the left ventricle (LV) to study the diastolic flow changes in TA. Real-time 3-dimentional echocardiography loops (ECHO) were acquired in normal control group, in TA patients before surgery (pre-op group) and after surgery (post-op group). ECHO loops were reconstructed and simulated by CFD, the geometric, volumetric changes, and vortices in the LV were studies and compare among 3 groups. Compared with the control group, pre-op TA patients demonstrated significant LV remodeling, manifesting with smaller LV length, larger diameter, width and spherical index, as well as lager volumes; post-op TA group showed revisions in values of both geometric and volumetric measurements. CDF also demonstrated the abnormality of vortices in the pre-op TA patients and the alteration of existence and measurements of vortex in postoperation group. Echo-based CFD modeling can show the abnormality of TA in both LV geometric, volumetric measurements and intracardiac vortices; and CFD is capable to demonstrate the alterations of LV after Fontan and Glenn surgical procedure.